The stranger within: creating imagined communities in settler contexts: American New Orleans and Russian Odessa, 1803-1862 - Durand, O (2021)
The nineteenth century was marked by imperial competition on a global scale, both though oversea trading ventures and movements of colonisation across continents. Diasporic communities played a central role in empire-making, and their participation in settler colonialism encourages historical inquiries from below. These communities also participated in the creation of informal empires: such was the case of French political and economic émigrés, who settled within the recent territorial gains of other nations and became in turn actors of colonisation. Strangers within their own host communities, they rose to prominence primarily in urban settings, where they could rely on political opportunities and networks that granted them power and influence. In the United States, the Louisiana Purchase and the opening of Western lands to American settlement transformed the formerly marginal role of New Orleans’ francophone Creoles. They became an ambiguous internal other, both aiding and challenging American rule. In the Russian Empire, the conquest and settlement of the Black Sea shores was overseen by French administrators and traders. Most settled in the new city of Odessa and created an urban order that set the city apart from customary Russian rule. Early Odessa and New Orleans were both marked by the influence of francophone groups, located at the intersection with wider immigration patterns, logics of urban growth, and the combination of national politics with empire-building. All contributed to the creation of cities on the margin, estranged from their own nations. This thesis proposes a Francophone and Frenchified ethos as a valuable social currency, which directed the development of key urban institutions such as churches, schools, and newspapers. From the 1800s to the mid-century, that French paradigm was trialled through national and international events, which detached the purposes and meaning of Frenchness from France itself. French attributes – through language and practices – became transformative tools that were a central feature of early New Orleans and Odessa. The two cities witnessed the development of a re-invented Frenchness outside of a formal French realm, which created a flexible category that was only valid within their respective cityscapes. This research points to the multiplicity of actors and scales in each urban context, as well as to the layering of meanings of concepts of Frenchness, historical agency, and empire. Ultimately, the findings of the thesis open promising avenues for the further study of diasporic imperialisms and the function of language and cultural institutions in both supporting and challenging state-driven colonial projects.